INFLUENCE OF HEALTH ENERGY SERVICES AND CONFIDENCE ON PATIENT SUCCESSIONS IN THE PROVISIONS OF EASTERN LAMP - Sugiono Sugiono; Dede Dede; Hikmatul Aliyah Hikmatul Aliyah; Riyan Ferdiyansah (Journal of Research in Social Science and Humanities, 2024)
The success and success of the role of a health institution is to serve the community or the patient well and properly in order to improve the health and nutritional status of the community so that the people can feel comfort, security and can increase the satisfaction and confidence in the health institution. The study is entitled “Pengruh trust and medical service to patient satisfaction in the Puskesmas of Pakuan Aji Lampung East. The purpose of this study is to know the influence of trust and service performed jointly – equally (simultaneously) or individually (partially) on the satisfaction of patients in Puskesmas Pakuan Aji. This research is a type of quantitative research using pursiposive sampling techniques to collect data, the population in this study are patients Puskesmas Pakun Aji Lampung East. And as many as 100 people were responding to this study, as well as using a dual linear regression analysis tool with the SPSS 25 application. Based on the results of the T-Test that the confidence variable (X1) has a significant influence on patient satisfaction (Y) and the health care variables (X2) have a significant impact on patients satisfaction(Y). On the basis of the test F on this study, it can be concluded that the trust variable(X1) and health care services(X2) together (simultaneously) have a positive and significant effect on the patient’s satisfaction variable. (Y).